How does the use of GLP-1 receptor agonists affect bone mineral density and fracture risk in obese individuals? - Zalewski, Jakub Zbigniew; Cyrzan, Alicja; Styczyńska , Małgorzata; Iwanowska, Martyna; Flis, Beata; Zysk, Adam; Ząbek, Mateusz; Goss, Adrian; Fronczak, Bartosz; Wojewódzki, Maciej (Journal of Education, Health and Sport, 2026)
Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are an important group of drugs widely used in the treatment of type 2 diabetes and obesity. Studies indicate their beneficial effect on glycemic control and weight reduction, as well as potential involvement in bone metabolism modulation. The aim of this review was to evaluate the current knowledge regarding the impact of GLP-1RAs on bone mineral density (BMD) and fracture risk. A narrative literature review with elements of systematic searching was conducted, covering clinical and observational studies from 2015 to 2025. The available data indicate that GLP-1RAs do not cause a significant decrease in BMD compared to placebo or insulin glargine. Some studies observed a slight increase in bone resorption markers, which did not translate into clinically relevant decreases in BMD. Cohort studies data suggest a potential decreased risk of osteoporosis among GLP-1RA-treated population. Current literature confirms the overall safety of GLP-1RA therapy in the context of bone health, although further long-term studies are necessary to fully clarify their effects on bone microarchitecture and fracture risk.